2006
DOI: 10.1177/097172180601100202
|View full text |Cite
|
Sign up to set email alerts
|

Technological Behaviour and Export Probability in Developing Countries

Abstract: This article studies innovative behaviour and its impact on export activity. Our results show—for the Mexican case—that innovation is a method used to meet international standards and is therefore necessary in order to compete in export markets. This relationship has been observed in both developed and developing countries, although the exact configuration differs, probably due to the different role innovation plays in each. We used several sub-samples showing that different types of firms are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Scholars found complementarities between the use of advanced technologies and both product and process innovation (Musolesi & Huiban, ), a significant and positive influence on process innovation but not on product (Hall, Lotti, & Mairesse, ; Tang, ), or else no significant relations at all either with product or with process innovation (Amara, Landry, & Doloreux, ). With regard to internationalization, while some scholars found that the use of advanced technologies increase internationalization probability (Estrada & Heijs, ), others found nonsignificant relations (Lal, ). This leads to the development of hypotheses H6 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars found complementarities between the use of advanced technologies and both product and process innovation (Musolesi & Huiban, ), a significant and positive influence on process innovation but not on product (Hall, Lotti, & Mairesse, ; Tang, ), or else no significant relations at all either with product or with process innovation (Amara, Landry, & Doloreux, ). With regard to internationalization, while some scholars found that the use of advanced technologies increase internationalization probability (Estrada & Heijs, ), others found nonsignificant relations (Lal, ). This leads to the development of hypotheses H6 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Aunque parece haber, también, alguna influencia de la localidad. Esta situación puede estar relacionada con los diferentes resultados e interpretaciones de los modelos explicativos de la probabilidad y propensión exportadora (Estrada 2005, Estrada y Heijs, 2006. Mientras que en los primeros las capacidades de aprendizaje e innovación tienen un claro efecto, en los segundos, es probable, que estas capacidades estén mediadas por el capital relacional.…”
Section: Análisis De Resultadosunclassified
“…Likewise, Özçelik and Taymaz, (2004) found similar results for Turkish firms, where product innovativeness was not significant in explaining their export propensity. On the contrary, Estrada and Heijs (2006) found that product innovation strategy had a negative effect on Mexican firms' export propensity.…”
Section: Hypotheses Development 21 Product Innovation Capability As a Driver Of Internationalisationmentioning
confidence: 89%